2020
DOI: 10.1049/iet-map.2020.0387
|View full text |Cite
|
Sign up to set email alerts
|

Transmission of a broadband FSK signal from a dynamically tuned narrowband antenna

Abstract: A frequency reconfigurable patch antenna is dynamically tuned to transmit frequency-shift keying (FSK) signals over a range of frequencies much broader than the static impedance bandwidth of the antenna. Experiments are conducted for two binary FSK schemes having different carrier spacing. In both cases, dynamic tuning of the antenna is shown to increase the amplitude of the radiated signal by providing a better match than the static antenna. However, the average energy of the radiated bit at each carrier freq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Frequency shift keying (FSK) is of particular interest for DAM schemes because it requires the most bandwidth for a given data rate while being relatively energy efficient. While the DAM concept was originally developed for FSK at very low frequency [7][8][9][10][11][12], it was recently rediscovered for higher frequency FSK systems and demonstrated in several different papers [13][14][15][16][17][18]23]. It is mentioned in several prior studies that energy storage and transfer is fundamental to the scheme but a model and quantitative understanding of how energy storage (or lack thereof) affect the signal characteristics has not been investigated in much detail.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Frequency shift keying (FSK) is of particular interest for DAM schemes because it requires the most bandwidth for a given data rate while being relatively energy efficient. While the DAM concept was originally developed for FSK at very low frequency [7][8][9][10][11][12], it was recently rediscovered for higher frequency FSK systems and demonstrated in several different papers [13][14][15][16][17][18]23]. It is mentioned in several prior studies that energy storage and transfer is fundamental to the scheme but a model and quantitative understanding of how energy storage (or lack thereof) affect the signal characteristics has not been investigated in much detail.…”
Section: Introductionmentioning
confidence: 99%
“…It is mentioned in several prior studies that energy storage and transfer is fundamental to the scheme but a model and quantitative understanding of how energy storage (or lack thereof) affect the signal characteristics has not been investigated in much detail. In a recent experimental study [18], the present authors investigated a rapidly tuned antenna for 2‐FSK and 4‐FSK transmissions in which energy was not stored and transferred between states due to the high carrier frequency relative to the slow switching time and lack of phase synchronization. While this approach is flexible in implementation and frequency scaling, our analysis showed that the lack of stored energy in the system results in long characteristic charging time between states, and restricts the symbol rate to the bandwidth of the most narrowband antenna state.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The basis of DAM overcomes the high Q-factor of ESAs traditionally limited by linear time invariant (LTI) matching circuits through time-varying operation. The time-varying operation enables the RF energy on the antenna to be directly modulated through the direct integration of switching circuits on an ESA, which enables transmission of highbandwidth signals such as amplitude shift keyed [9,[11][12][13][14][15][16][17], phase shift keyed [18,19] and frequency shift keyed (FSK) [10,[20][21][22][23][24][25][26][27][28][29] signals.…”
Section: Introductionmentioning
confidence: 99%